A NONLINEAR ITERATIVE LEARNING-METHOD FOR ROBOT PATH CONTROL - BIEN, ZN; HWANG, DH; OH, SR (CAMBRIDGE UNIV PRESS, 1991)
An iterative learning control method is proposed for a class of non-linear dynamic systems with uncertain parameters. The method, in which non-linear system model is used, employs the model algorithmic control concept in the iteration sequence. A sufficient condition for convergency is provided. Then the method is shown to be applicable to continuous-path control of a robot manipulator.